Development of irtawsi: A User-Friendly R Package for IRT Analysis - Susanto, Hari Purnomo; Agus Maman Abadi; Haryanto; Retnawati, Heri; Ali, Rade Muhammad; Djidu, Hasan (FAKULTAS PSIKOLOGI UIN SYARIF HIDAYATULLAH JAKARTA, 2025)
The complexity of the IRT analysis makes it difficult to perform manually, therefore requiring easy-to-use software. While many software options exist for IRT analysis, the high cost of paid software can make it inaccessible for many students and lecturers in Indonesia. While the mirt package provides a complete, free option for IRT analysis, proficiency in the R programming language is required. This study aims to develop an R package for IRT analysis, equipped with a user-friendly interface based on the mirt package, designed to be easy to use for beginners in IRT analysis. The System Development Life Cycle (SDLC) model is used for development and includes five stages: Planning, Analysis, Design, Implementation, and System. The resulting package is named irtawsi and includes functionality comparable to paid software. This package can calibrate both test and non-test instruments using various IRT models, such as the Rasch, 2PL, 3PL, 4PL, GRM, PCM, and GPCM models. The irtawsi package functionality includes: (1) an easy-to-use user interface, (2) automatic interpretation of analysis results, (3) a guide for IRT analysis, (4) recommendations when assumptions are not met, (5) an HTML report format for analysis results,(6) support for two languages (Indonesian and English), (7) it is free, and (8) can be installed on Windows, macOS, and Linux operating systems. The results of this development contribute to the calibration process, making it easier for practitioners and researchers to calibrate the instruments being developed, especially for beginners who are learning IRT.